Vectorization on Intel Xeon PHI : A Survey - Thool, Akhilesh; Channe, Hemlata (International Journal of Computer Sciences and Engineering, 2025)
Intel Xeon Phi coprocessors are the new family members of processors and platforms to the Intel family. Intel Xeon Phi is the first in the family of Intel MIC (Many Integrated Core) architecture. Software running on the coprocessor should leverage innumerable cores as well as make use of wide SIMD operation. Vectorization is the process of converting an algorithm from scalar implementation to vector. It is the form of parallel programming where the processors perform same operation simultaneously on N data elements of vector i.e. one dimensional array of scalar data objects such as floating point object , integers or double integers floating point. When the hardware is coupled with C/C++ compiler that supports it, developers have easier time delivering more efficient and better performing software.